Mild hypothermia with selective antegrade cerebral perfusion during cardiopulmonary bypass and short-term outcomes in children with congenital heart defects - Utpal S Bhalala; Pranali Awadhare; Malarvizhi Thangavelu; Richard Owens; Maria Zamora; Daniel Nento; Elumalai Appachi; Muhammad Ali Mumtaz (Wolters Kluwer Medknow Publications, 2021)
Background: Among the known risk factors for children undergoing surgery for congenital heart defect (CHD), temperature and blood flow during cardiopulmonary bypass (CPB), are two risk factors, which may be altered to improve outcomes. Moderate - to - deep hypothermia (MDH), traditionally used, has been associated with short/long-term neurologic sequelae, so there is a move towards mild hypothermia (MH) with selective antegrade cerebral perfusion (SACP). Aims and Objectives: To assess feasibility of mild hypothermia with selective antegrade cerebral perfusion during cardiopulmonary bypass as a cardiopulmonary bypass strategy in neonates and infants undergoing surgery for congenital heart defect. Materials and Methods: We conducted a retrospective chart review of neonates and infants who underwent SACP on CPB during CHD surgery at our tertiary care children's hospital between January 2014 and February 2017. We categorized all the patients into 2 groups - MH + SACP or MDH + SACP. We gathered data on preoperative, intra-operative and post-operative parameters. We analyzed comparative data using student t-test and chi-squared test with a significant p-value < 0.05. Results: There were 6 in the MH + SACP group and 7 in the MDH + SACP group, who underwent SACP on CPB during study period at our children's hospital. All the neonates and infants in the MH + SACP group survived at the hospital discharge with favorable neurologic outcomes. There was no statistically significant difference between the two groups for end organ dysfunction, ventilator days, hospital days, ICU and hospital mortality and PCPC/POPC at hospital discharge. Conclusions: Mild hypothermia with selective antegrade cerebral perfusion during cardiopulmonary bypass is a feasible cardiopulmonary bypass strategy in neonates and infants undergoing surgery for congenital heart defect.